Pilot-Scale Production of Cellulosic Nanowhiskers With Similar Morphology to Cellulose Nanocrystals - Wang, Huihui; Zhu, Jonathan J.; Ma, Qianli; Agarwal, Umesh P.; Gleisner, Roland; Reiner, Richard; Baez, Carlos; Zhu, J. Y. (Frontiers in Bioengineering and Biotechnology, 2020)
This study describes a class of cellulosic nanomaterials, cellulosic nano whiskers (CNWs), and demonstrates scaled-up production with acid recovery using less expensive equipment made of common stainless steel rather than glass-lined steel. CNWs produced using concentrated maleic acid (MA) hydrolysis followed by mechanical fibrillation have morphology similar to MA-produced cellulose nanocrystals (CNCs) and sulfuric-acid-produced CNCs (S-CNCs) but differ in crystallinity. Applications of CNWs as a substitute for CNCs for which morphology and surface charge, rather than crystallinity, are the pertinent characteristics are presented. The tested CNW suspensions have a wider viscosity range of 0.001 to 1000 Pa.s over a variety of shear rates of 0.01 to 1000 1/s compared to S-CNCs of 0.001 to 0.1 Pa.s and are better suited for applications such as rheology modification and 3D printing. This study proposes CNWs as a less expensive and more sustainable replacement for CNCs in applications that do not require crystalline properties.